2011
DOI: 10.1093/pubmed/fdr034
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of the NHS Health Checks programme in a deprived, culturally diverse setting: cross-sectional study

Abstract: Uptake of cardiovascular risk assessment and prescribing of statins in high risk patients was considerably lower than projected in the first year of NHS Health Checks programme. Targeting efforts to increase uptake and adherence to interventions in high risk populations and reinvesting resources into population wide strategies to reduce obesity, smoking and salt intake may prove more cost-effective in reducing the burden of cardiovascular disease in the UK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
119
4
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(132 citation statements)
references
References 27 publications
8
119
4
1
Order By: Relevance
“…If the intervention was rolled out in clinical practice, higher rates would be expected; for example, uptake rates to the NHS Health Check Programme, 228 which is not a research project, are double those reported in this and other research screening studies. Future research should focus on increasing uptake to screening in all groups.…”
Section: Strengths and Limitationsmentioning
confidence: 72%
“…If the intervention was rolled out in clinical practice, higher rates would be expected; for example, uptake rates to the NHS Health Check Programme, 228 which is not a research project, are double those reported in this and other research screening studies. Future research should focus on increasing uptake to screening in all groups.…”
Section: Strengths and Limitationsmentioning
confidence: 72%
“…Dalton et al 25 reported a 45% uptake of health checks in west London. This was consistent with experience in south London, where uptake was running at < 40%.…”
Section: Uptake Of the Nhs Health Check Programmementioning
confidence: 99%
“…Higher deprivation has been linked with lower uptake, 61 which is consistent with evidence from other screening programmes, 16 whereas some studies have reported higher uptake in more deprived areas 27 or no relationship. 25 In the same trial, 25 the proportion of health checks and demographic characteristics were compared between patients who received a postal invitation and those whose health checks were performed opportunistically.…”
Section: Uptake Patternsmentioning
confidence: 99%
“…For example, the NHS Health Check programme has a 40% uptake rate. 206 A full discussion of the uptake to screening is given in Chapter 6. Future studies should look at methods for increasing the uptake to screening, particularly in hard-to-reach groups.…”
Section: Randomised Controlled Trial Resultsmentioning
confidence: 99%
“…The NHS Health Check programme, which is not part of a research project, has seen uptake rates of around twice the level that we have reported here. 7,206 Second, everyone received an OGTT. The OGTT is costly, time-consuming and inconvenient.…”
mentioning
confidence: 99%